THE RIGHTS OF LAND IN MARRIAGE AGREEMENT ACCORDING TO THE CONSTITUTIONAL COURT DECISION NUMBER 69 / PUU-XIII 2015 BASED ON THE CUSTOMARY LAW PERSPECTIVE - Miqat, Nurul; Patittingi, Farida (Yustisia, 2018)
The definition of marriage is provided in Article 1 that: "Marriage is a mental bond between a man and a woman as husband and wife with the aim of forming a happy, eternal, (family) family based on the One Supreme God." The meaning of marriage under the law, Law Number 1 Of 1974 is a marriage has a very close relationship with religion, spirituality, so that marriage not only has the element of birth / body, but the element of spirit / rokhani also has a very important role. The legal consequence of a marriage is the position of a woman who becomes a wife and a man becomes a husband, hence the rights and obligations assumed by both after the legal act of marriage. For those who marry most do not think about the effects of marriage, on their wealth, some of them only think that the consequences of marriage are only the union of two families, and the continuity of their marriage in order to be eternal and happy. Marital Laws Article 35 to Article 37 regulate about the field of marriage property for husbands and wives, Affirmation of Article 35 states that marriage property becomes a common property. While the property of each luggage as a gift or inheritance, is under the control of each. Unless otherwise specified in order to serve as joint property, for this other determination the husband and wife are allowed to make "marriage agreement", this marriage agreement contains about marriage property. Likewise to the perpetrators of miscenegations. Indonesian citizens who marry foreign citizens, not knowing that there are legal consequences of such miscenegations, there is a right to be lost as a result of miscenegation. The rights in question relate to the marriage agreement, which if the perpetrator of a miscenegation does not enter into a marriage agreement will impact on land rights , and it is also known  under costumary law.